Preparation method of liquid rubber heat-conducting and energy-storing adhesive, adhesive and application method

By using adhesives combined with low-functional liquid rubber and bifunctional curing agent, combined with composite phase change materials and thermal fillers, the problem of poor stability of existing thermal management adhesives in high temperature environments is solved, and an adhesive with high thermal conductivity, energy storage functions and good mechanical properties is achieved, which is suitable for a variety of application scenarios.

CN119709047APending Publication Date: 2025-03-28XIANHE NEW MATERIAL (SUZHOU) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411903581.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing thermal management adhesives have shortcomings in taking into account both thermal conductivity, energy storage, mechanical properties and breadth of application, especially in high-temperature environments such as poor stability, easy liquefaction, and insufficient adhesive properties.

Method used

A liquid rubber thermal energy storage adhesive with a dual-functional curing agent is used to combine with composite phase change materials and thermal fillers. Through specific preparation methods and process steps, a liquid rubber thermal energy storage adhesive with high thermal conductivity, energy storage functions and good mechanical properties is prepared.

Benefits of technology

It has achieved stability in high temperature environments, is not easy to liquefy and oil seepage, has good mechanical properties and a wide range of application methods, and can simultaneously realize potting, coating, bonding and gasket production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005203835830000031
    Figure BDA0005203835830000031
  • Figure BDA0005203835830000061
    Figure BDA0005203835830000061
  • Figure BDA0005203835830000091
    Figure BDA0005203835830000091
Patent Text Reader

Abstract

The invention discloses a preparation method of a liquid rubber heat-conducting and energy-storing adhesive, the adhesive and an application method. The raw materials used in the preparation method comprise liquid rubber, a heat-conducting filler, an auxiliary agent, phase-change wax or a composite phase-change material and a curing agent or a cross-linking agent. The molecular weight of the liquid rubber is less than 6000, the viscosity is less than 20000 cps, the functionality of a reactive group in the liquid rubber is less than or equal to 3, and the Tg point of the crosslinked liquid rubber is lower than-40 DEG C. The composite phase change material is formed by mixing phase change wax and a phase change capsule, and the melting points of the phase change wax and the phase change capsule are less than or equal to 65 DEG C. According to the scheme, the balance among heat conduction, energy storage, mechanical performance and economic performance can be solved; and the coating also has the characteristics of low cost, convenience in production, potting, coating, calendaring molding and the like, and can be applied to different production processes and application scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of thermal conductive adhesives, and in particular to a preparation method of a liquid rubber thermal conductive energy storage adhesive, an adhesive and an application method. Background Art

[0002] With the demand for new energy, lightweight and high integration of electronic devices, adhesives in thermal management materials need to be applied to more diverse scenarios. By effectively solving the balance between thermal conductivity, energy storage, mechanics and economic performance, effective heat management can be achieved to improve equipment performance, life and heat utilization.

[0003] Existing thermal management adhesives mainly include thermal conductive interface materials, thermal conductive phase change materials and shaped thermal conductive phase change materials, among which:

[0004] Thermal interface materials include thermal conductive gel, thermal conductive silicone grease, thermal conductive gasket, thermal conductive potting glue, etc. The production technology of this type of material is relatively mature. For example, the invention patent with publication number CN116410569A discloses a thermal conductive gel with high thermal conductivity and high anti-aging performance and its preparation method, which uses a compound of aluminum oxide and zinc oxide to improve thermal conductivity; and by adding an appropriate amount of silicon carbide, silicon dioxide and epoxy resin, silicon carbide, silicon dioxide and epoxy resin can enhance the anti-aging performance of thermal conductive aggregation. However, this type of material is mainly used to improve thermal conductivity. It has no enthalpy change, and heat dissipation needs to rely on external aluminum or copper heat dissipation components. It has no energy storage function, so the application of conventional thermal interface materials in the field where energy storage and thermal conductivity need to be taken into account is limited.

[0005] Thermally conductive phase change materials include phase change pastes, phase change sheets, etc. It is mainly achieved by compounding phase change wax with thermally conductive materials such as graphene, boron nitride, aluminum powder, aluminum oxide, carbon fiber, carbon nanotubes, and modified graphite. While retaining thermal conductivity, it has a certain energy storage effect. For example, a phase change thermal conductive material and its preparation method disclosed in the invention patent with authorization announcement number CN111303838B are prepared by mixing graphite powder, aluminum nitride powder, zinc oxide powder, aluminum oxide powder, magnesium oxide, paraffin, polyethylene, ethylene-vinyl acetate copolymer, glass fiber, flame retardant, coupling agent, and toughening agent. It has high thermal conductivity and can improve heat dissipation effect. However, there are still a series of problems: first, the materials used, especially carbon materials, are expensive; second, this type of material has no adhesive properties and is limited in market application; third, after the material is formed, if heated, it will cause liquefaction and flow. At the same time, the phase change paste also needs to be diluted with volatile solvents, which can easily cause pollution; fourth, this type of material has poor toughness and is brittle at low or room temperature, and this is more obvious after use; fifth, the material density is generally lower than 3g / ml, and the high thermal conductivity phase change has low heat absorption and release energy per unit volume.

[0006] The shaped thermally conductive phase change material is mainly phase change capsule material. This type of material is to coat the phase change wax with organic or inorganic materials, and the appearance is powder. When heated, it still maintains the powder state, avoiding the problem of high-temperature liquefaction and flow of conventional phase change wax. For example, the invention patent with the authorization announcement number CN111359554B discloses a large-particle polyurethane phase change microcapsule and its preparation method, which produces a phase change microcapsule with an average particle size greater than 100μm, good thermal stability and good density. The current problem is that the mechanical properties of the phase change capsule are poor, it is easy to break under pressure or shear, the filling amount of the thermal conductive powder is limited, the thermal conductivity is generally low, the resin is silicone or polyol polyurethane resin, the finished product has poor mechanical properties and poor toughness; at the same time, the simple phase change capsule does not have thermal conductivity, and the powder state is not suitable for direct application. It generally needs to be matched with an adhesive. The finished product is mostly in the form of a fixed-size gasket, which is not suitable for potting or heterogeneous area application.

[0007] In addition, some existing thermal conductive paste materials are mixed with non-reactive inert carrier oil or resin and phase change materials such as paraffin and thermal conductive fillers. In this type of thermal conductive paste material, since the carrier oil or resin that accounts for a large proportion of the raw materials has no reaction activity, no cross-linking structure is formed in this type of raw material system, or only the weak reaction of the system produces cross-linking to inhibit the release of the inert carrier oil. Therefore, this type of adhesive always has an obvious problem of inert oil release in a high temperature environment, and it is very easy to soften and deform or liquefy and leak oil, and must be stored in a refrigerated manner; at the same time, some resin materials have extremely poor compatibility with paraffin, and cannot be mixed and solidified. Summary of the invention

[0008] Therefore, in order to solve the above problems, a preparation method, adhesive and application method of a liquid rubber thermal conductive energy storage adhesive are provided, which has high thermal conductivity, energy storage function, good mechanical properties, is easy to use and has a wide range of applications, and can simultaneously achieve potting, coating, bonding and gasket production.

[0009] The present invention is achieved through the following technical solutions:

[0010] A method for preparing a liquid rubber heat-conducting energy-storing adhesive, comprising liquid rubber, heat-conducting filler, additive, phase-change wax or composite phase-change material and curing agent or cross-linking agent; the molecular weight of the liquid rubber is less than 6000, the viscosity is less than 20000 cps, the functionality of the reactive groups in the liquid rubber is ≤3 and the Tg point of the liquid rubber after cross-linking is lower than -40°C, the composite phase-change material is formed by mixing phase-change wax and phase-change capsules, and the melting points of the phase-change wax and phase-change capsules are ≤65°C;

[0011] The method comprises the following preparation steps:

[0012] Step 1: Stir and dissolve the phase change wax and liquid rubber at a temperature of 70°C-100°C to prepare resin A, and keep resin A in liquid state;

[0013] Step 2: Mix the curing agent or cross-linking agent at a temperature of 70°C-100°C and evenly, and then cool it into a paste B for later use;

[0014] Step 3: Add thermal conductive filler to liquid resin A and stir evenly, then add phase change capsule and stir evenly, and form paste C after cooling;

[0015] Step 4: Mix paste B and paste C evenly, vacuum seal and store at a temperature of less than 30°C.

[0016] Preferably, the following components are included in parts by mass:

[0017]

[0018] The thermal conductive filler includes one or a mixture of aluminum powder, aluminum oxide, ceramic powder, aluminum hydroxide, magnesium hydroxide, zinc oxide, iron oxide, graphene, graphite, silver powder, copper powder, nickel powder, silicon dioxide, carbon fiber, copper fiber, aluminum fiber, and hexagonal boron nitride.

[0019] Preferably, the thermally conductive filler comprises large-particle zinc oxide with a median particle size of ≥4 μm and / or submicron zinc oxide with a particle size of 0.7 μm-1.2 μm.

[0020] Preferably, the thermally conductive filler comprises a mixture of dendritic copper powder and / or nickel powder with a particle size of 10μm-40μm and / or chopped metal fibers with a diameter of 5μm-20μm and a length of 0.5mm-1.5mm, large-particle zinc oxide with a median particle size of ≥4μm, and submicron zinc oxide with a particle size of 0.7μm-1.2μm, wherein the chopped metal fibers comprise one or more of copper wire, nickel wire, zinc wire, and aluminum wire. In the thermally conductive filler, the total added amount of zinc oxide accounts for >70wt%, and the total added amount of metal fibers and dendritic copper powder and / or nickel powder accounts for <25wt%.

[0021] Preferably, the zinc oxide is surface pretreated by adding a long-chain silane coupling agent accounting for 0.2%-0.6% of the powder mass, and the dendritic copper powder and / or nickel powder is surface pretreated by adding Tween or fatty acid surfactant.

[0022] Preferably, the curing agent is a difunctional isocyanate curing agent.

[0023] Preferably, the auxiliary agent includes at least one of an antioxidant, a flame retardant, a solvent, a dehydrating agent, a catalyst and a coupling agent.

[0024] Preferably, the phase change capsules are organically coated and / or inorganically coated.

[0025] The liquid rubber thermal conductive energy storage adhesive is prepared by any of the above-mentioned preparation methods of the liquid rubber thermal conductive energy storage adhesive.

[0026] The application method of the liquid rubber thermal conductive energy storage adhesive comprises the following steps:

[0027] Step I: Prepare the liquid rubber thermal conductive energy storage adhesive as described above;

[0028] Step II: stirring the liquid rubber thermal conductive energy storage adhesive uniformly at a temperature of 70° C. to 100° C.;

[0029] Step III: Fill, dispense or apply the stirred liquid rubber thermal conductive energy storage adhesive to the glue coating area, and cool it to shape at room temperature; or apply the liquid rubber thermal conductive energy storage adhesive to the gasket molding equipment, and cover the upper and lower films, and calender it through the calendering equipment.

[0030] The beneficial effects of the technical solution of the present invention are mainly reflected in:

[0031] 1. This solution uses low-functionality liquid rubber and a bifunctional curing agent to facilitate control of the cross-linking strength, thereby ensuring the softness of the adhesive after curing, alleviating the internal stress caused by the large expansion coefficient of the phase change capsule, and having a high elongation at break, thereby ensuring the stability of the mechanical properties of the material. The main chain of the liquid rubber is a diene or an olefin, and its main chain is a linear structure or a rocker structure, which has good compatibility with paraffin wax, so as to reduce the viscosity at high temperature after mixing and increase the powder filling degree. At the same time, due to the good solubility of the liquid rubber and the phase change wax, wax precipitation and a significant attenuation of mechanical properties are avoided; in addition, in the present invention, due to the presence of reactive groups in the liquid rubber and the controllable cross-linking reaction strength of the reactive groups, it can ensure that the liquid rubber has a certain reactivity while ensuring its softness after curing. Since the liquid rubber is combined with the curing agent to form a cross-linking structure, the phase change material is prevented from liquefying at high temperature, and its mechanical properties are enhanced, so that the adhesive is not easily deformed by force after curing.

[0032] 2. Adding a composite phase change material, wherein the composite phase change material includes a phase change wax and a phase change capsule, wherein the phase change capsule can be coated with an organic and / or inorganic material, and a low-viscosity resin is used in combination with the composite phase change material, thereby ensuring that the mixed resin can achieve a lower viscosity at a temperature greater than 65°C, and achieve a higher phase change capsule filling rate while having an enthalpy value. At the same time, the low-viscosity finished product can greatly reduce damage to the phase change capsule, thereby achieving no precipitation of paraffin under high temperature conditions and ensuring the stability of the product morphology. In addition, the composite phase change material has good compatibility with the low-viscosity resin, which can avoid mechanical attenuation caused by phase separation.

[0033] 3. Thermal conductive fillers can be mixed with large-particle zinc oxide and submicron zinc oxide as potting glue or adhesive, or dendritic metal powder and chopped metal fiber can be mixed with large-particle zinc oxide and submicron zinc oxide as thermal conductive energy storage pad materials. The application methods are diversified. The non-spherical filler morphology has better thermal conductivity than the spherical one at the same filling amount. Zinc oxide and dendritic metal powder can be surface treated to increase the compatibility of metal powder and resin, thereby enhancing the mechanical properties of the adhesive.

[0034] 4. Low-temperature baking or moisture curing can be used. By mixing the curing agent or catalyst with the phase change wax to form a paste, the risk of moisture absorption failure of isocyanate curing agents or titanate catalysts can be reduced. At the same time, single-component packaging is more convenient than traditional two-component packaging, easy to use, and can also avoid waste. DETAILED DESCRIPTION

[0035] In order to make the purpose, advantages and features of the present invention more clearly and in detail, the following non-limiting description of the preferred embodiment will be used for explanation. The embodiment is only a typical example of the application of the technical solution of the present invention, and any technical solution formed by equivalent replacement or equivalent transformation falls within the scope of protection claimed by the present invention.

[0036] In addition, the terms "first" and "second" in this solution are only used for descriptive purposes and cannot be understood as indicating or implying the order of importance, or implicitly indicating the number of technical features shown. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0037] The invention discloses a preparation method of a liquid rubber heat-conducting energy-storing adhesive, comprising liquid rubber, heat-conducting filler, additive, phase change wax or composite phase change material and curing agent or cross-linking agent; the molecular weight of the liquid rubber is less than 6000, the viscosity is less than 20000cps, and the liquid rubber needs to have reactive groups, such as hydroxyl, alkoxy, isocyanate, carboxyl, anhydride, etc.; the functionality of the reactive groups is ≤3, so as to control the cross-linking strength and obtain a soft polymer. At the same time, by controlling the cross-linking reaction strength, problems such as softening or oil seepage of the adhesive at high temperature can be avoided.

[0038] The liquid rubber forms an elastomer with a Tg point below -40°C after cross-linking, and has excellent low-temperature resistance and good mechanical properties. In some embodiments, the selectable liquid rubber types include but are not limited to: liquid polybutadiene (polybutadiene, terminal hydroxyl polybutadiene, alkoxy-modified polybutadiene, acrylic acid-modified polybutadiene, isocyanate-modified polybutadiene, anhydride-modified polybutadiene, etc., carboxyl-modified polybutadiene), liquid polyisoprene, carboxyl-modified polyisoprene, anhydride-modified polyisoprene.

[0039] The composite phase change material is formed by mixing phase change wax and phase change capsules, and the melting points of the phase change wax and the phase change capsules are ≤65°C; in one embodiment, the phase change wax includes but is not limited to paraffin wax and soybean wax having a melting point in the range of 35-65°C. In some embodiments, the phase change capsules are organically coated and / or inorganically coated, wherein the phase change capsules are preferably organically coated and have a phase change wax with high latent heat, such as polyurethane coated phase change capsules (such as polyurethane coated n-docosane, whose liquefaction temperature is 40°C-60°C), followed by inorganic coated phase change wax, such as silica coated phase change capsules; the strength of the phase change capsules is relatively low and they are prone to failure due to shear breakage. The use of liquid rubber resin with low viscosity and phase change wax with good compatibility can improve its mechanical properties, achieve a higher phase change capsule filling rate while having an enthalpy value, avoid the destruction of the phase change capsules, thereby achieving no precipitation of paraffin under high temperature conditions and ensuring the stability of the product form.

[0040] In some embodiments, the preparation method of the liquid rubber thermal conductive energy storage adhesive includes the following components in parts by mass:

[0041]

[0042] The thermal conductive filler includes one or a mixture of aluminum powder, aluminum oxide, ceramic powder, aluminum hydroxide, magnesium hydroxide, zinc oxide, iron oxide, graphene, graphite, silver powder, copper powder, nickel powder, silicon dioxide, carbon fiber, copper fiber, aluminum fiber, and hexagonal boron nitride.

[0043] In one embodiment, the thermally conductive filler includes large-particle zinc oxide with a median particle size of ≥4 μm (preferably large-particle zinc oxide with a particle size of 6 μm-20 μm) and / or submicron zinc oxide with a particle size of 0.7 μm-1.2 μm. The above materials are used as adhesives for thermally conductive fillers for easy dispensing, so they can be used as thermally conductive potting glue or direct dispensing. When the large-particle zinc oxide and submicron zinc oxide are mixed for use, the amount of large-particle zinc oxide added is more than twice the amount of submicron zinc oxide added.

[0044] In another embodiment, the thermally conductive filler comprises a mixture of a metal filler having a bridging effect and zinc oxide, for example, a mixture of dendritic copper powder and / or nickel powder with a particle size of 10 μm-40 μm and / or a short-cut metal fiber with a diameter of 5 μm-20 μm and a length of 0.5 mm-1.5 mm and zinc oxide, wherein the zinc oxide comprises large-particle zinc oxide with a median particle size of ≥4 μm (preferably large-particle zinc oxide with a particle size of 6 μm-20 μm) and / or submicron zinc oxide with a particle size of 0.7 μm-1.2 μm. When large-particle zinc oxide and submicron zinc oxide are mixed for use, the addition amount of the large-particle zinc oxide is more than twice the addition amount of the submicron zinc oxide, the chopped metal fiber includes one or more of copper wire, nickel wire, zinc wire, and aluminum wire, and in the thermal conductive filler, the total addition amount of the zinc oxide accounts for more than 70wt%, and the total addition amount of the metal fiber and the dendritic copper powder and / or nickel powder accounts for less than 25wt%. By adding a filler with a bridge, the thermal conductivity is improved at the same filling amount. When the above material is used as a thermal conductive filler, it can be used as a thermal conductive energy storage pad after rolling and curing.

[0045] In the above embodiments, in order to increase the compatibility of the thermally conductive filler with the liquid rubber, the thermally conductive filler is first surface pretreated to increase the compatibility of the metal powder with the resin, thereby enhancing the mechanical properties of the adhesive, wherein the zinc oxide is surface pretreated by adding a long-chain silane coupling agent accounting for 0.2%-0.6% of the powder mass, and the dendritic copper powder and / or nickel powder is surface pretreated by adding Tween or fatty acid surfactant.

[0046] In some embodiments, the curing agent is a difunctional isocyanate curing agent, such as MDI, HDI, HMDI, TMDI, etc.

[0047] In some embodiments, the auxiliary agent includes at least one of an antioxidant, a flame retardant, a solvent, a water scavenger, a catalyst and a coupling agent; wherein the water scavenger includes p-methylbenzenesulfonyl isocyanate, calcium oxide, triethyl orthoformate, oxazolidine, etc.; the antioxidant includes hindered phenol antioxidants such as: BASF antioxidant 245, antioxidant 1010, antioxidant 1035, antioxidant 1076 and antioxidant 1135, etc., and can also be used in combination with phosphite auxiliary antioxidants, such as: antioxidant 168; the flame retardant is preferably an aliphatic phosphate flame retardant; the solvent is selected from isomerized alkanes with good compatibility with liquid rubber, low-viscosity solvent oil, etc.; the catalyst can be environmentally friendly catalysts such as titanate, organotin, organozirconium, organoaluminum compounds, zinc bismuth, etc., preferably titanate and / or organotin, and by mixing the curing agent or catalyst with the phase change wax to form a paste, the risk of moisture absorption failure of the isocyanate curing agent or titanate catalyst can be reduced.

[0048] The preparation method of the liquid rubber thermal conductive energy storage adhesive comprises the following preparation steps:

[0049] Step 1: Stir and dissolve the phase change wax and liquid rubber at a temperature of 70°C-100°C to prepare resin A, and keep resin A in liquid state;

[0050] Step 2: Mix the curing agent or cross-linking agent and the phase change wax at a temperature of 70°C-100°C and evenly, and then cool to form a paste B for later use;

[0051] Step 3: Add thermal conductive filler to liquid resin A and stir evenly, then add phase change capsule and stir evenly, and form paste C after cooling;

[0052] Specifically, a stirring device with oil bath heating is used to heat and mix to form liquid resin A, paste B and paste C. The specific stirring temperature, stirring speed and stirring time can be adjusted according to actual needs and will not be described in detail here.

[0053] Step 4: After mixing paste B and paste C evenly, vacuum seal them and store them at a temperature of less than 30°C; wherein, since the phase change wax can block the reaction at room temperature, there is no need to use two-component packaging, which can simplify the application steps; after mixing the paste B and paste C, they are preferably sealed and stored in a thickened version of RCPP, PET, PA, NY / PE and other materials with good temperature resistance. The vacuum bags are degassed and sealed, and stored at a temperature of less than 30°C; when in use, the vacuum bags sealed with liquid rubber thermal conductive energy storage adhesives can be placed in a 70°C-85°C oven for heating and liquefaction, and after mixing evenly using a vibration device or wearing scald-proof gloves, a corner can be cut and the adhesive can be poured or applied to the required area.

[0054] The present invention also discloses a liquid rubber thermal conductive energy storage adhesive, which is prepared by any of the above-mentioned preparation methods of the liquid rubber thermal conductive energy storage adhesive.

[0055] According to the preparation method of the above-mentioned liquid rubber thermal conductive energy storage adhesive, the liquid rubber thermal conductive energy storage adhesive is prepared according to the material ratios of the following Examples 1-8; at the same time, comparative examples 9-15 with different raw materials and ratios from the above-mentioned preparation method are provided, and the specific materials used in each embodiment and comparative example are as follows:

[0056] A: Resin:

[0057] A1: Polybd R45V polybutadiene liquid rubber, produced by Craywell, A2: POLYVEST EP ST silane-terminated liquid polybutadiene, produced by Evonik Industries, A3: 9102 liquid silicone, produced by Anhui Handie Electronic New Materials Co., Ltd., A4: PPG400 / 2000 polypropylene glycol, produced by Tianjin Meida Petrochemical Co., Ltd.;

[0058] B: Curing agent (isocyanate curing agent):

[0059] B1: MDI-50, produced by Wanhua Chemical, B2: TYZOR 9000, India DorfKetal Chemical Co., Ltd. (DorfKetal), B3: SUPRASEC 2647, produced by Huntsman Polyurethane (China) Co., Ltd.;

[0060] C: Auxiliary agent:

[0061] Antioxidant: C1: Antioxidant 245, produced by BASF;

[0062] Flame retardant: C2: TCPP, produced by Jiangsu Yak Technology Co., Ltd.;

[0063] Catalyst: C3: polyurethane catalyst AUCAT-101, produced by Guangzhou Yourun Synthetic Materials Co., Ltd.;

[0064] D: Phase change wax:

[0065] D1: refined paraffin wax, produced by PetroChina Kunlun brand; D2: soybean wax (Soy Wax), produced by Dongguang County Ziyang Beeswax Products Factory;

[0066] E: Phase change capsule:

[0067] E1: TH-ME phase change microcapsules, produced by Hubei Saimo New Energy Technology Co., Ltd., E2: PCM phase change microcapsules (PCM45), produced by Hefei Xinneng Phase Change New Material Technology Co., Ltd.;

[0068] F. Thermally conductive filler:

[0069] F1: large particle size (median particle size ≥ 4 μm) calcined zinc oxide, produced by Shiroshige Chemical and Sakai Chemical Industry Co., Ltd.

[0070] F2: chopped copper fiber, homemade copper wire with a diameter of 5μm-20μm and a length of 0.5mm-1.5mm;

[0071] F3: zinc oxide (particle size 0.7 μm-1.2 μm), produced by Shandong Xingyuan Zinc Industry Technology Co., Ltd. Table 1: Material ratios of Examples 1-5;

[0072]

[0073] Table 2: Material ratios of Example 6-Example 9;

[0074]

[0075]

[0076] Table 3: Material ratios of Comparative Examples 10-13;

[0077]

[0078] Table 4: Material ratios of Comparative Examples 14-16;

[0079]

[0080] Among them, the preparation steps of each embodiment and the comparative example are the same, and the corresponding adhesive products are obtained. The adhesive products are placed in containers respectively, and the containers are heated to 70°C-100°C and stirred evenly. After laminating the upper and lower films, they are prepared into 2mm thick sheets by calendering equipment; wherein, the adhesive products prepared by embodiments 1-4 and comparative examples 9-15 are baked and cured in an ordinary electric oven, the curing temperature is 70°C, the curing time is 4 hours, or placed at room temperature for 5 days; embodiments 5-8 adopt moisture curing method, and are placed in an environment with a relative humidity of 60±10RH% at room temperature for 7 days, and the cured sheets are tested as follows:

[0081] 1. Thermal conductivity: Tested according to ASTM D5470;

[0082] 2. Enthalpy test: Test according to method GB / T 19466.5-2022;

[0083] 3. Hardness test: Test according to method GB / T 2411-2008;

[0084] 4. Toughness test: bend the 1mm thick sheet at 90° and 180° respectively, and observe whether there are cracks after folding;

[0085] 5. Oil penetration test: Place the cured sheet on filter paper and place it at 100°C for 24 hours to observe whether it liquefies or leaks oil.

[0086] The test results are as follows:

[0087] Table 5: Test results of Examples 1 to 9;

[0088]

[0089] Table 6: Comparative Examples 10-16 test results;

[0090]

[0091]

[0092] In Table 6 above: when the enthalpy value is less than 5J / ml, it is judged as NG; when the cured material is bent 90° and the appearance of the material is damaged, the "toughness, 90°" test is NG; when the cured material is bent 180° and the appearance of the material is damaged, the "toughness, 180°" test is NG; when the hardness is ≥90, it is NG; when the hardness is ≥70, it is judged to be easily broken.

[0093] It should be noted that due to the poor compatibility between resin and paraffin, they cannot be mixed evenly and solidified into shape, so resin and paraffin cannot be tested as raw materials at the same time.

[0094] According to the above test results, the liquid rubber thermal conductive energy storage adhesive prepared by the preparation method of the liquid rubber thermal conductive energy storage adhesive disclosed in the present invention has a thermal conductivity of 0.3W / mk-5W / mk, an enthalpy of 5J / ml-200J / ml, and a hardness of less than 70 (Shao A) after curing; compared with the comparative example, it has multiple advantages: first, after curing, it takes into account both thermal conductivity and energy storage, is a flexible solid, does not liquefy when heated, and does not leak oil; second, the product has a high enthalpy value, which can reduce temperature shock while dissipating heat from power components; third, it has good toughness, does not fall off, does not liquefy at high temperatures, and does not produce oil; it can solve the balance between thermal conductivity, energy storage, mechanics, and economic performance; in addition, it also has the characteristics of low cost, convenient production, potting, coating, and calendering, and can be applied to different production processes and application scenarios; fourth, the single-component room temperature sealed packaging form can simplify the current requirement that the AB components need to be packaged separately, as well as the process of weighing and proportioning before use.

[0095] Among them, compared with the embodiments and Examples 14 to 16, Comparative Examples 10 to 13 do not add curing agents and catalysts, and their physical properties are weak, their toughness is poor, they cannot withstand heat and are easily deformed; Compared with the embodiments, Comparative Examples 14 to 16 use polypropylene glycol instead of polybutadiene liquid rubber. Due to the poor compatibility of polypropylene glycol with phase change materials such as paraffin, the two components are easily mixed unevenly, or mechanical attenuation occurs due to phase separation.

[0096] The present invention also discloses an application method of a liquid rubber thermal conductive energy storage adhesive, comprising the following steps:

[0097] Step I: Prepare the liquid rubber thermal conductive energy storage adhesive as described above;

[0098] Step II: stirring the liquid rubber thermal conductive energy storage adhesive uniformly at a temperature of 70° C. to 100° C.;

[0099] Step III: potting, dispensing or coating the stirred liquid rubber thermal conductive energy storage adhesive on the glue-coated area, and cooling it at room temperature to set the shape; or coating the liquid rubber thermal conductive energy storage adhesive on the gasket molding equipment, and laminating it on the upper and lower films, and calendering it through the calendering equipment; referring to the above-mentioned embodiments 4, 5, 7 and 9, the thermal conductive material includes zinc oxide of different particle sizes and short-cut copper fibers, so it is suitable for curing after calendering and use as a thermal conductive energy storage pad; and other embodiments use zinc oxide as the thermal conductive material, which can be used as a potting glue or direct dispensing.

[0100] There are many implementation methods of the present invention, and all technical solutions formed by equivalent transformation or equivalent transformation fall within the protection scope of the present invention.

Claims

1. A method for preparing a liquid rubber thermal conductive energy storage adhesive, characterized in that: The invention comprises liquid rubber, thermal conductive filler, additive, phase change wax or composite phase change material and curing agent or cross-linking agent; the molecular weight of the liquid rubber is less than 6000, the viscosity is less than 20000cps, the functionality of the reactive group in the liquid rubber is less than 3 and the Tg point of the liquid rubber after cross-linking is less than -40°C, the composite phase change material is formed by mixing phase change wax and phase change capsules, and the melting points of the phase change wax and phase change capsules are less than 65°C; The method comprises the following preparation steps: Step 1: Stir and dissolve the phase change wax and liquid rubber at a temperature of 70°C-100°C to prepare resin A, and keep resin A in liquid state; Step 2: Mix the curing agent or cross-linking agent at a temperature of 70°C-100°C and evenly, and then cool it into a paste B for later use; Step 3: Add thermal conductive filler to liquid resin A and stir evenly, then add phase change capsule and stir evenly, and form paste C after cooling; Step 4: Mix paste B and paste C evenly, vacuum seal and store at a temperature of less than 30°C.

2. The method for preparing the liquid rubber thermal conductive energy storage adhesive according to claim 1, characterized in that: It includes the following components by mass: 3-50 parts of liquid rubber resin; Curing agent 0.4-10 parts; Additives 0.1-1 part; Phase change wax 2-50 parts; Phase change capsules 0-50 parts; Thermally conductive filler 40-94 parts; The thermal conductive filler includes one or a mixture of aluminum powder, aluminum oxide, ceramic powder, aluminum hydroxide, magnesium hydroxide, zinc oxide, iron oxide, graphene, graphite, silver powder, copper powder, nickel powder, silicon dioxide, carbon fiber, copper fiber, aluminum fiber, and hexagonal boron nitride.

3. The method for preparing the liquid rubber thermal conductive energy storage adhesive according to claim 2, characterized in that: The thermally conductive filler comprises large-particle zinc oxide with a median particle size of ≥4 μm and / or submicron zinc oxide with a particle size of 0.7 μm-1.2 μm.

4. The method for preparing the liquid rubber thermal conductive energy storage adhesive according to claim 2, characterized in that: The thermally conductive filler comprises a mixture of dendritic copper powder and / or nickel powder with a particle size of 10μm-40μm and / or short-cut metal fibers with a diameter of 5μm-20μm and a length of 0.5mm-1.5mm, large-particle zinc oxide with a median particle size of ≥4μm, and submicron zinc oxide with a particle size of 0.7μm-1.2μm, wherein the short-cut metal fibers comprise one or more of copper wire, nickel wire, zinc wire, and aluminum wire. In the thermally conductive filler, the total addition amount of zinc oxide accounts for more than 70wt%, and the total addition amount of metal fibers and dendritic copper powder and / or nickel powder accounts for less than 25wt%.

5. The method for preparing the liquid rubber thermal conductive energy storage adhesive according to claim 3 or 4, characterized in that: The zinc oxide is surface pretreated by adding a long-chain silane coupling agent accounting for 0.2%-0.6% of the powder mass, and the dendritic copper powder and / or nickel powder is surface pretreated by adding Tween or fatty acid surfactant.

6. The method for preparing the liquid rubber thermal conductive energy storage adhesive according to claim 1, characterized in that: The curing agent is a difunctional isocyanate curing agent.

7. The method for preparing the liquid rubber thermal conductive energy storage adhesive according to claim 1, characterized in that: The auxiliary agent includes at least one of an antioxidant, a flame retardant, a solvent, a dehydrating agent, a catalyst and a coupling agent.

8. The method for preparing the liquid rubber thermal conductive energy storage adhesive according to claim 7, characterized in that: The phase change capsules are organically coated and / or inorganically coated.

9. Liquid rubber thermal conductive energy storage adhesive, characterized by: The liquid rubber thermal conductive energy storage adhesive is prepared by the preparation method of any one of claims 1 to 8.

10. The application method of the liquid rubber thermal conductive energy storage adhesive is characterized by: The following steps are involved: Step I: preparing the liquid rubber thermal conductive energy storage adhesive as described in claim 9; Step II: stirring the liquid rubber thermal conductive energy storage adhesive uniformly at a temperature of 70° C. to 100° C.; Step III: Fill, dispense or apply the stirred liquid rubber thermal conductive energy storage adhesive to the glue coating area, and cool it to shape at room temperature; or apply the liquid rubber thermal conductive energy storage adhesive to the gasket molding equipment, and cover the upper and lower films, and calender it through the calendering equipment.

Citation Information

Patent Citations

  • A phase change thermal conductive material and its preparation method

    CN111303838B

  • A large-particle-size polyurethane phase change microcapsule and its preparation method

    CN111359554B

  • Heat-conducting gel with high heat conductivity and high aging resistance and preparation method of heat-conducting gel

    CN116410569A